Optimization of GMA Welding Process Parameters During the Welding of IS 2062 steel by Taguchi Technique - Dr. Saadat Ali Rizvi; Wajahat Ali (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
The main objective of research works is to optimize the GMA welding parameters which affect the mechanical properties of IS 2062 structural steel weldment. Taguchi technique, a soft computing approach was applied to optimize the process parameters. A total of sixteen numbers of experiments have been conducted. For this purpose, L16 orthogonal array was used. Analysis of variance (ANOVA) was applied to determine the effect of process parameters such as arc voltage, gas flow rate, and wire feed speed on weld quality. Tensile strength, and microhardness, were examined to determine the mechanical properties of weldment. From the result, it has been noticed that the tensile strength and hardness of weldment are significantly affected by arc voltage while gas flow rate has an insignificant effect.
Keywords: Taguchi Technique; Mechanical Properties; Optimization; ANOVA; IS 2062 steel